RELATIONSHIP BETWEEN FAMILY HISTORY OF HYPERTENSION AND SMOKING HABITS WITH INCIDENCE OF HYPERTENSION AMONG ADOLESCENTS IN PALEMBANG - Zahwan Maulana Mawardy; Andra Kurnianto; Puji Rizki Suryani (Majalah Kedokteran Sriwijaya, 2021)
Hypertension does not only occur in adults, but 3-5% occurs in adolescents so early detection of hypertension is very important to reduce complications due to hypertension. Family history of hypertension and smoking habits have been proven to be a risk factor for hypertension in adolescents. This study aims to determine the relationship between family history of hypertension and smoking habits with Incidence of Hypertension Among Adolescent in Palembang.The research conducted was observation research with cross sectional study design. Using primary data which obtained from blood pressure measurements and filling out questionnaires. The sample of this study were students from 12 high schools in Palembang who met the inclusion criteria and did not meet the exclusion criteria with a total sample of 515 students. The results of the chi-square analysis showed that there was significant relationship between family history of hypertension with Incidence of Hypertension Among Adolescent (p=0,000; PR=3,299; 95% CI= 2,906-7,265). And there was no significant relationship between smoking habits with Incidence of Hypertension Among Adolescent (p=1,000; PR=0,916; 95% CI= 0,293-2,735) in Palembang.